The First Constitutional Government of the Minnesota Anishinaabeg - Krausová, Anna (Text Matters: A Journal of Literature, Theory and Culture, 2018)
In this paper I trace the development of Native American constitutionalism in the early twentieth century. Specifically, I focus on the first constitutional government of the White Earth Nation, located in northwestern Minnesota, which in the period from 1913 to 1927 was part of a larger confederative arrangement, called the General Council of the Chippewa. The purpose of this paper is to show the importance of this inter-reservation government for the preservation of White Earth Anishinaabe cultural continuity from which revitalization efforts of the late twentieth and early twenty-first century grew. Using archival resources, I pay attention to Anishinaabe governing practices and their ethical dimension that can be understood in the light of Anishinaabe philosophy which was an integral part of everyday life. My findings suggest that the course of institutional development set by the creation of the General Council in 1913 influenced the path of White Earth governance for the rest of the century.